Powertrain Instrumentation and Test Systems Development - Hybridization - Electrification - Paulweber, Michael; Lebert, Klaus; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The book deals with the increasingly complex test systems for powertrain components and systems giving an overview of the diverse types of test beds for all components of an advanced powertrain focusing on specific topics such as instrumentation, control, simulation, hardware-in-the-loop, automation or test facility management. This book is intended for powertrain (component) development engineers, test bed planners, test bed operators and beginners.
Introduction -- Types of test beds -- Hardware perspective -- Software perspective: Test bed -- Test facility.
Keywords: Automotive engineering; Engines; Transportation engineering; Traffic engineering; Automotive Engineering; Engine Technology; Transportation Technology and Traffic Engineering